Humanization as a paradigm of contemporary international relations system - Raev D. S., Sarsenov M. B., (Opción, 2020)
This work studies the theoretical problems of international relations development in conditions of globalization. The main factors of the humanization of the current international relations system are characterized via comparative qualitative research methods. As a result, pragmatism and political realism deny the identification of certain nations’ aspirations with world moral laws. It is concluded that there are enough opportunities for the humanization process in modern international relations.